Comparison of Vascular Complications in Patients with Percutaneous Coronary Intervention by Trans-radial and Trans-femoral Approach (Bangladesh Heart Journal, 2019)
Background and Objective: Trans-radial approach of coronary catheterization has been increasingly used as an alternative to transfemoral approach due to less vascular complications, earlier ambulation and improved patient comfort. The aim of the study was to compare procedural and post procedural vascular complications in patients with percutaneous coronary intervention by trans-radial and transfemoral approach.Methods: This observational comparative study was conducted in the National Institute of Cardiovascular Diseases between June 2015 to May 2016. A total of 180 patients were categorized into two groups according to the approach of the percutaneous coronary intervention (PCI). Group I comprising 90 patients who underwent trans-radial PCI and group II consists of 90 patients who underwent transfemoral PCI. Patients with an abnormal Allen’s test, acute coronary syndrome, history of coronary artery bypass surgery, chronic renal insufficiency or older age (>75 years) were excluded.Results: Patient demographics were the same in both groups. The mean procedural time in min (37.44±5.13 vs 34.14±4.42, p=0.004) and fluoroscopy time in min (21.62±4.11 vs 17.55±2.78, p=0.02) were more in TR-PCI group but the mean haemostasis time in min (7.58±1.11 vs 15.59±3.33, p=0.005) and ambulation time in hour (0.00±0.00 vs 15.59±3.33, p=